2023
DOI: 10.1021/acs.langmuir.3c00616
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Adsorbed to the Air–Water Interface Form Soft Glasses

Abstract: When monoclonal antibodies are exposed to an air−water interface, they form aggregates, which negatively impacts their performance. Until now, the detection and characterization of interfacial aggregation have been difficult. Here, we exploit the mechanical response imparted by interfacial adsorption by measuring the interfacial shear rheology of a model antibody, anti-streptavidin immunoglobulin-1 (AS-IgG1), at the air−water interface. Strong viscoelastic layers of AS-IgG1 form when the protein is adsorbed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…An exponential dependence of the elastic modulus is observed in concentrated colloidal gels and glasses as described elsewhere. 34,36 Naturally then, the observation of visible particle counts also correlates with the protein concentration in this hydrophobic region at the interface, showing a linear correlation with an R 2 of 0.96 as shown in Figure 7B. The total amount of absorbed protein (i.e., the total volume fraction of mAb at the interface) also correlates with the interfacial elastic modulus and visible particle counts, as shown in Figure S8 (Supporting Information).…”
Section: X-ray Reflectometrymentioning
confidence: 70%
See 3 more Smart Citations
“…An exponential dependence of the elastic modulus is observed in concentrated colloidal gels and glasses as described elsewhere. 34,36 Naturally then, the observation of visible particle counts also correlates with the protein concentration in this hydrophobic region at the interface, showing a linear correlation with an R 2 of 0.96 as shown in Figure 7B. The total amount of absorbed protein (i.e., the total volume fraction of mAb at the interface) also correlates with the interfacial elastic modulus and visible particle counts, as shown in Figure S8 (Supporting Information).…”
Section: X-ray Reflectometrymentioning
confidence: 70%
“…At hydrophobic interfaces such as the air–water interface, proteins are believed to undergo conformational change to expose hydrophobic residues to the hydrophobic phase (i.e., air in this system) and lower overall free energy. , This structural rearrangement leads to enhancement in hydrophobic interactions with the tightly packed, neighboring molecules, giving rise to the β-sheet formation, as has been confirmed for some hydrophobins and monoclonal antibodies. , As discussed, the interfacial elastic (or storage) modulus is a metric to quantify the interprotein interaction at the air–water interface, which could reflect the long-term instability (or particulate formation propensity) of antibodies in solution . Thus, it is reasonable to interpret the enhancement in interprotein interactions at the interface as probed by interfacial rheology as being due to strong interprotein hydrophobic attractions, such as β-sheet formation, as indicated by significant enhancement in protein concentration in the hydrophobic region at the air interface, as shown by the strong peak in the XRR measurements.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, Wood et al. studied the response to the application of shear stress to a mAb film formed at the air–water interface and showed that the protein film formed a soft glass at the air–water interface . More recently, Pham et al also correlated the rheology of industrially relevant mAbs to their long-term stability under storage conditions .…”
Section: Introductionmentioning
confidence: 99%